PENGGUNAAN OBAT DIABETES MELLITUS PADA PASIEN RAWAT JALAN YANG MENJALANKAN HEMODIALISA - Erna Prasetya Ningrum (Parapemikir : Jurnal Ilmiah Farmasi, 2022)
Kidney dysfunction causes diseases including chronic kidney failure (CKD), where the state of decreased kidney function in the body is quite severe. CKD is permanent or irreversible damage, the damage that occurs cannot be repaired or returned to normal [12]. Based on the cause, kidney failure is caused by several diseases, including diabetes mellitus by 44% [12]. One of the main causes of chronic kidney failure in people with diabetes mellitus, the existence of a hyperglycemic state where several co-morbidities appear including disorders of the retina of the eye, cardiovascular, neuro [10]. The purpose of the study was to determine the number of kidney failure patients who underwent hemodialysis who received antihyperglycemic drugs, classes, and doses. The research method, the data collection was done retrospectively, the sample was taken by purposive sampling. The results showed that based on the sex of men as much as 31.58% and women by 68.42%, ages 46-55 years as many as 84.21%, single drug use by 81%, use of glycuidon dose of 30 mg by 33%. Conclusion of the data obtained The use of the drug glycuidone is relatively safe to use for patients with diabetes mellitus with kidney complications who are undergoing hemodialysis. The use of insulin in DM-complicated CKD patients will affect the state of blood insulin